Blade pitching in vertical axis wind turbines: A double multiple stream tube theoretical approach to performance enhancement - Antim Gupta; Ussama Ali; Hamid Ait Abderrahmane; Isam Janajreh (Heliyon)
This research delves into the performance enhancement of Vertical Axis Wind Turbines (VAWTs) through the innovative approach of variable blade pitching based on Double Multiple Stream Tube theory principles. VAWTs, known for their potential in urban and low-wind environment, often face efficiency and energy yield challenges. This study addresses these challenges by proposing a novel variable blade pitching mechanism that dynamically adapts to changing wind conditions, optimizing the aerodynamic performance, and enhancing the torque and overall performance of VAWT rotor. The efficiency of two pitching models is investigated on 3-bladed NACA0015 rotors, where the blade's local angle of attack is cyclically adjusted below the stall angle to maximize the lift force and torque throughout full revolution. In Model 1, the angle of attack experiences cyclic variation as a sinusoidal function providing smooth pitching, whereas in Model 2, the peak value of angle of attack was fixed below the stall condition forming linear function. The investigation showed substantial improvement in the VAWT performance using both pitching models. The variable blade pitching strategy significantly enhances the lift-to-drag ratio and thus improving the torque output across diverse wind scenarios/tip speed ratios, demonstrating its effectiveness in maximizing the operational efficiency of VAWTs. Blade pitching model 1 and 2 were found to be effective across all lower Tip Speed Ratio (TSR) values, suggesting its robustness in variable wind conditions. A peak average coefficient of performance (Cp) of 0.568 was achieved at TSR = 5 using pitching Model 1 with a maximum angle of attack of 8.5°, compared to a Cp of 0.48 for the fixed blade configuration, near to Betz's limit (Cp = 0.593). The findings confirm that integrating variable blade pitching would substantially improve VAWT performance and offer a clear direction for revolutionary future wind turbine aerodynamic design enhancements.